The Marketing Information System and Its Importance in the Success of Proactive Marketing: Sistem Informasi Pemasaran dan Perannya dalam Kesuksesan Pemasaran Proaktif - Mahmoud, Basheer Ismail (Indonesian Journal of Law and Economics Review, 2025)
General Background This study addresses the growing need for data-driven marketing practices in dynamic business environments. Specific Background Iraqi firms face limitations in proactive marketing due to underdeveloped marketing information systems. Knowledge Gap Empirical evidence explaining how marketing information systems support proactive marketing in this context remains limited. Aims This research aims to examine the relationship between marketing information systems and proactive marketing within Iraqi companies. Results Using a descriptive and analytical approach with questionnaire data from 126 respondents and SPSS analysis, the findings reveal a strong statistical relationship, with marketing information systems explaining a substantial proportion of variance in proactive marketing practices. Novelty The study provides empirical validation from an underrepresented regional context using comprehensive statistical testing. Implications The findings suggest that strengthening marketing information systems supports anticipatory marketing practices, informed decision-making, and organizational readiness in competitive markets. Keywords: Marketing Information System, Proactive Marketing, Decision Support Systems, Market Intelligence, Iraqi Firms Key Findings Highlights: Marketing data integration supports anticipatory market actions Statistical analysis confirms a strong system-based relationship Organizational readiness depends on structured information flows